The role of AI in academic writing: Unveiling strategies among EFL students - Brigita Griska Putri; Nunung Suryati; Francisca Maria Ivone; Nur Hayati (University of Muhammadiyah Malang, 2025)
Artificial Intelligence (AI) has received many positive perceptions for improving the quality of students’ academic writing, especially in the realm of English as a Foreign Language (EFL). However, the strategies students use to integrate AI into academic writing remain largely underexplored, especially in the Indonesian context. This study aims to unveil students' strategies in utilizing AI to improve the quality of their academic writing. It employed the qualitative case study design. The participants consisted of four EFL undergraduate students who were purposively selected based on three main criteria: 1) having completed an academic writing course, 2) using AI to assist their academic writing process, and 3) producing good academic writing outcomes. Data were collected through semi-structured interviews and user walkthroughs, and the transcripts were then analyzed thematically. The findings show that AI can assist students in four stages of the academic writing process, namely planning, drafting, revising, and editing. It supports idea generation, grammar correction, and improves writing style by promoting an academic tone. Students also report higher motivation and perceived improvements in writing performance. However, students felt less confident as they were worried that AI might reduce originality in their writing. Hence, this study provides insights into the use of AI in EFL students' academic writing strategies and highlights the importance balanced AI use to preserve originality, academic integrity, and critical thinking skills.